Enhancing photon absorption and conductivity of ZnO film by Fe doping: Experimental and first-principle perspectives. Issue 17 (1st December 2020) - Virdian, Angga; Muhammady, Shibghatullah; Naradipa, Muhammad A.; Widita, Rena; Rusydi, Andrivo; Darma, Yudi
Abstract: We study the optical and conductivity properties of Fe-doped ZnO (ZnO:Fe) film. ZnO and ZnO:Fe films (0.6 at. % and 1.2 at. % Fe concentration) were deposited using direct-current-unbalanced magnetron sputtering at room temperature. The presence of Fe dopant enhances the photon absorption of ZnO. The I–V and spectroscopic ellipsometry characteristic show that the electrical and optical conductivity of ZnO:Fe is increased. The first-principle calculation confirms the changes in the optical properties and conductivity due to Fe 3d states. The results show the role of Fe doping in modifying the optical and conductivity properties of ZnO film.